Industry chain and challenges of microalgal food industry-a review - Chen, Yuanhao; Liang, Honghao; Du, Hong; Jesumani, Valentina; He, Weiling; Cheong, Kit-Leong; Li, Tangcheng; Hong, Ting (Critical reviews in food science and nutrition, 2024)
Currently, the whole world is facing hunger due to the increase in the global population and the rising level of food consumption. Unfortunately, the impact of environmental, climate, and political issues on agriculture has resulted in limited global food resources. Thus, it is important to develop new food sources that are environmentally friendly and not subject to climate or space limitations. Microalgae represent a potential source of nutrients and bioactive components for a wide range of high-value products. Advances in cultivation and genetic engineering techniques provide prospective approaches to widen their application for food. However, there are currently problems in the microalgae food industry in terms of assessing nutritional value, selecting processes for microalgae culture, obtaining suitable commercial strains of microalgae, etc. Additionally, the limitations of real data of market opportunities for microalgae make it difficult to assess their actual potential and to develop a better industrial chain. This review addresses the current status of the microalgae food industry, the process of commercializing microalgae food and breeding methods. Current research progress in addressing the limitations of microalgae industrialization and future prospects for developing microalgae food products are discussed.